New records and unusual morphology of the cave hydrozoan Velkovrhia enigmatica Matjašič & Sket, 1971 (Cnidaria: Hydrozoa: Bougainvilliidae) - Maja Zagmajster; Teo Delić; Simona Prevorčnik; Valerija Zakšek (Natura Sloveniae)
Velkovrhia enigmatica is the only freshwater hydrozoan living exclusively in groundwater. It is endemic to the Dinarides in the Balkan Peninsula, where it has been known from four caves only. Here we report on a new V. enigmatica population from cave Logarček near Laze in southwestern Slovenia. In addition, after almost 30 years since its last recorded presence, we confirm the current presence of numerous V. enigmatica individuals in the type locality, Planinska jama. Individuals from the two caves were morphologically different: polyps from the type locality had 4–9 tentacles, while the ones from Logarček had 14–36 tentacles. The mitochondrial DNA sequences in populations from both caves did not differ. Additional research is needed to provide further insights into species taxonomy, biology and distribution.